Identificación de caracteres de preferencia en variedades de yuca por parte de usuarios de la cadena producción-consumo en la región Caribe colombiana - López Montes, Antonio José; Marín Arredondo, N. (2007)
The incorporation of end-user criteria in different links of the production-consumption chain has been broadly documented in the first link and with relation to plant breeding. However incorporating concepts in the research process from other links could guarantee a greater impact on productivity. The purpose of this research was two fold: 1) to identify preferred knowledge users characteristics in the different links of the cassava agrochain, and 2) to incorporate these traits in the design of new varieties. Evaluation of cassava clones was done by farmers and middlemen on farms, plant breeders evaluated at research centers, processors evaluated at chipping and drying plants and fresh cassava consumers at the household level. Through open interview, diverse opinions and traits were recorded and encoded to perform a multiple correspondence analysis. While male farmers achieved a proper differentiation between the best clones by their characteristics, women had less differentiation because they used more similar categories for most traits. At five localities, plant breeders selection of the best nine clones and their associated characters allowed for the identification of three groups of clones with desirable traits and two clones with undesirables characteristics. Common traits among the best clones evaluated by household consumers were associated with taste, pulp color, consistency and starch content. Analyses of common traits among all evaluators indicated that one axis was established by consumers and another by plant breeders. The results indicated that high starch content was the determining feature in clone selection for natural dryers, while for starch producers the most important traits were fresh weight/dry starch ratio and white skin color. At the end, common criteria were identified among dryers, household consumers, researchers and farmers gender.